Awareness of Orthodontic Treatment in School Children in Sirte, (Middle Region of Libya): A Cross-Sectional Study - Aftima Alamin Derbash (African Journal of Advanced Pure and Applied Sciences, 2024)
This study has been designed to assess the concerns of schoolchildren about receiving orthodontic care. To determine how well school students in Sirte City are informed of orthodontic issues and how they are treated. Since orthodontic therapy necessitates patient commitment and compliance, it is critical to evaluate patients’ awareness and understanding to get baseline data that will help patients and operators make decisions. So, determining the level of awareness about orthodontic therapy is essential. There are studies in the literature that assess orthodontic knowledge and awareness among schoolchildren in various societies, but none have been discovered that assess these concepts in the middle regions of Libyan society, according to researchers. In a population that included a cross-sectional, observational (non-experimental), descriptive questionnaire survey, Data for the evaluation of knowledge and awareness of orthodontic treatment were generated by the restructured questionnaires (15 objective questions). Statistical data was analyzed and categorized according to age, gender, and residence place. The study’s findings demonstrated that students’ awareness and comprehension of orthodontic therapy were below average. It was found that the level of awareness of orthodontics varied depending on a person’s gender. Conclusion: Orthodontic knowledge was assessed, and limitations in this field were found in Sirte City among schoolchildren.